GNSS TECHNOLOGY FOR RESEARCH OF DEFORMATIONS OF HYDROTECHNICAL INSTALLATIONS: GNSS TECHNOLOGY FOR RESEARCH OF DEFORMATIONS OF HYDROTECHNICAL INSTALLATIONS - Dobrev, Stefan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
Hydro technical installations are subject to a list of temporary and constant factors, such as Natural, Physical, Tectonic, Anthropogenic and other, which lead to their deformation and destruction. Study, exploration and forecast of deformations, can save us big. In this article has been researched the GNSS capability of obtaining the necessary data for building a model and reading or predicting deformations. GNSS has been used for monitoring structural deformation and deflection for more than a 30 years now. Detailed procedures for field data collection, data analysis and visualisation, generation of reliable analytical model, model updating and prediction for structural operational condition are also recommended.